Prevalence and risk factors of computer vision syndrome—assessed in office workers by a validated questionnaire - Cantó-Sancho, Natalia; Porru, Stefano; Casati, Stefano; Ronda, Elena; Seguí-Crespo, Mar; Carta, Angela (PeerJ, 2023)
Background Computer vision syndrome (CVS) is a common occupational health problem, but its clinical definition, prevalence and risk factors are not well defined. In general, non-validated diagnostic instruments have been used to assess its prevalence. For this reason, the aim of this study is to estimate the prevalence and potential risk factors for CVS using a validated questionnaire. Methods A cross-sectional study (n = 238) was carried out in Italian office workers using digital devices. All participants responded to an anamnesis, a digital exposure questionnaire, and the validated Italian version of the Computer Vision Syndrome Questionnaire. A battery of 3 ocular surface and tear ophthalmic tests (break-up time, BUT), Schirmer II and corneal staining) was performed. Results The mean age (±SD) was 45.55 (11.02) years, 64.3% were female. 71.4% wore glasses to work, whose design was monofocal (for distance) in 47.6%, monofocal (for near) in 26.5%, general progressive in 16.5% and occupational progressive in 8.8% of cases. 35.7% used digital devices >6 hours/day in the workplace. The prevalence of CVS was 67.2%. In the multivariate model, female sex (aOR: 3.17; 95% CI [1.75–5.73]), the use of digital devices >6 hours/day at workplace (aOR: 2.07; 95% CI [1.09–3.95]) and the use of optical correction at work (aOR: 2.69; 95% CI [1.43–5.08]) significantly increased the odds of CVS. Association was observed between presenting CVS and having abnormal BUT (χ2 = 0.017). Conclusions The prevalence of CVS in Italian office workers, especially among females, was high. Intensive use of digital devices at work (>6 hours/day) and the use of optical correction at work significantly increased the odds of CVS. There is an association between poor tear stability and CVS. Further research is needed on the influence of wearing optical correction on CVS. The use of a validated questionnaire in health surveillance of digital workers is strongly recommended.
Keywords: Computer vision syndrome; Digital devices; Office workers; Prevalence; Validated questionnaire; Ophthalmic test